Giving Processed Gonad of Sea Urchins and Skipjack Fish (Katsuwonus pelamis) to Stunted Children: Acceptability and Effectiveness - Hariani, Hariani; Fathurrahman, Teguh; Wiralis, Wiralis; Astuti, Trina; Imanuddin, Imanuddin (Public Health of Indonesia, 2025)
Background:Stuntingis a critical chronic nutritional issue prevalent in developing countries, including Indonesia, with profound effects on children's physical growth, cognitive development, and future productivity. Objective: This study aims to assess the acceptability of nuggets formulated from sea urchin gonads (Diadema setosum) and skipjack fish (Katsuwonus pelamis) as a nutritional supplement for addressing stunting in children under five years of age. Methods: A quantitative descriptive approach was employed, utilizing organoleptic testing. The study involved 161 panelists comprising nutrition students and mothers of toddlers attending the Posyanduin Soropia District, Konawe Regency. Results: The organoleptic test results indicated that the nuggets were well-accepted in terms of color, aroma, taste, and texture. A majority of the panelists rated them as "like" or "very like". Statistical analysis using a paired sample t-test demonstrated significant differences in acceptability before and after nugget administration across all assessed aspects (p< 0.05). Conclusion: Nuggets derived from sea urchin gonads and skipjack fish exhibit substantial potential as an alternative food supplement for stunted children, given their high acceptability and nutritional composition supporting growth and development. Further research is recommended to explore the long-term effects of regular nugget consumption on nutritional status and physical growth in stunted children, along with an economic analysis to evaluate the cost-effectiveness of this intervention.   Keywords:acceptability; organoleptic; nugget; sea urchin gonads; skipjack fish; toddler stunting